Commercial satellite imagery comes of age - FLORINI, Ann (Institutional Knowledge at Singapore Management University, 1999)
Since satellites started photographing Earth from space nearly four decades ago, their images have inspired excitement, introspection, and, often, fear. Like all information, satellite imagery is in itself neutral. But satellite imagery is a particularly powerful sort of information, revealing both comprehensive vistas and surprising details. Its benefits can be immense, but so can its costs.